The Influence of Social Media Platforms on Industrial Relations in the Nigerian Breweries Plc: Opportunities and Challenges (Abuja Journal of Sociological Studies, 2026)
This paper discusses how social media affects industrial relations in the Nigerian Breweries Plc based in Benin city, Edo state. The organization as a leading player in the beverage industry in Nigeria provides a good example to explore how digital platforms alter the process of communication and relationship within the organization. Using a quantitative research design, 480 of the employees were sampled using stratified methods and surveyed using structured questionnaires in order to determine the roles played by Facebook, X, LinkedIn, and Instagram in the process of developing communication, engagement, and collaboration. The results reveal that social media enhances the efficiency of communication, motivates employees to participate and strengthens organizational cohesion in the workplace. However, issues like privacy issues, fake news, and the unwillingness towards digital adoption are major obstacles to successful integration. The research suggests that detailed policies of digital communication and continuous education of employees should be taken in order to maintain the positive effect of social media but decrease the risks involved.The study can provide a conceptual model on the use of social media as a strategic means of developing harmonious and creative industrial relations by aligning the theoretical understanding with the reality.On the whole, the paper contributes to the body of existing knowledge about digital transformation in industrial relations by providing practical information to organizations and policymakers.